(untitled) (Ágora de Heterodoxias, 2023)
This essay presents preliminary reflections in relation to the new worldview of being within the framework of current epistemology. The purpose is to analyze the concept of being to understand how it is configured from another fundamental concept of philosophy: truth, theoretically approaching a definition of being, pondering about existence or non-existence. Through an analytical documentary review, it begins with a brief historical overview of the distinction of being by four authors who have dealt with the concept at different historical moments: Parmenides, Aristotle, Saint Thomas Aquinas and Heidegger, concluding that the denial of truth implies the denial of being.